1997
DOI: 10.1016/s0735-1097(97)00226-x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Persistent Left Ventricular Dysfunction During Recovery After Dobutamine Stress Echocardiography

Abstract: We demonstrated that normalization of left ventricular RWMAs occurs after resolution of symptoms and ECG changes during recovery. The time to recovery is related to the extent of CAD and myocardial ischemia as well as to the presence or absence of collateral circulation. These findings may represent stunned myocardium after brief period of ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The fact that these investigators showed a mismatch between function (depressed) and coronary perfusion (restored) further supports the concept that relatively brief episodes of demand-induced ischemia can result in stunned myocardium in humans. Recently, other forms of stress testing have been shown to cause stunning in 74,75 Stunned myocardium most certainly occurs after reperfusion for acute myocardial infarction, but this picture is complicated by a heart that contains both irreversibly injured cells (necrosis) and cells that have been reversibly injured by ischemia/reperfusion, the salvaged myocardium. The analysis by Reimer and Jennings 76 showed that after an abrupt coronary artery occlusion, there is a progressive wave front of cell death in the left ventricle that moves across the wall of the heart from the subendocardial to subepicardial layer (see Figure 1).…”
Section: Clinical Evidence For Stunned Myocardiummentioning
confidence: 99%
“…The fact that these investigators showed a mismatch between function (depressed) and coronary perfusion (restored) further supports the concept that relatively brief episodes of demand-induced ischemia can result in stunned myocardium in humans. Recently, other forms of stress testing have been shown to cause stunning in 74,75 Stunned myocardium most certainly occurs after reperfusion for acute myocardial infarction, but this picture is complicated by a heart that contains both irreversibly injured cells (necrosis) and cells that have been reversibly injured by ischemia/reperfusion, the salvaged myocardium. The analysis by Reimer and Jennings 76 showed that after an abrupt coronary artery occlusion, there is a progressive wave front of cell death in the left ventricle that moves across the wall of the heart from the subendocardial to subepicardial layer (see Figure 1).…”
Section: Clinical Evidence For Stunned Myocardiummentioning
confidence: 99%
“…4 Furthermore, an important advantage of these tracers over thallium 201 is the possibility of repeating the scan acquisition in case of major patient motion or other causes of inadequate image quality, without the risk of changes in perfusion. The duration of stress-induced functional impairment is controversial, [5][6][7][8][9][10] and scanty data are available about the time course of functional changes after exercise in gated SPECT poststress images. 3 It is therefore unclear what the rate of missed functional ischemic changes would be if the poststress acquisition had to be delayed (eg, because of persistent high subdiaphragmatic activity) or repeated (eg, because of excessive patient motion).…”
mentioning
confidence: 99%
“…Previously, Tsoukas et al [15] studied the presence of myocardial ischaemia during the recovery phase of DSE. Their results showed that patients with extensive coronary artery disease have more prolonged ischaemia.…”
Section: Discussionmentioning
confidence: 99%